Christian Perspectives on Transhumanism and the Church Chips in the Brain, Immortality, and the World of Tomorrow (Palgrave Studies in the Future of Humanity and its Successors, 2018)
Christians have always been concerned with enhancement-now they are faced with significant questions about how technology can help or harm genuine spiritual transformation. What makes traditional and technological enhancement different from each other? Are there theological insights and spiritual practices that can help Christians face the challenge of living in a technological world without being dangerously conformed to its values? This book calls on Christians to understand and engage the deep issues facing the church in a technological, transhumanist future.